Designing a Microservices-based Project Management System at XYZ Institute - Maleakhi, Felix Reinhard (Eduvest - Journal of Universal Studies, 2025)
This study focuses on the analysis and design of a Project Management System (PMS) for the XYZ Institute’s Research Department. The current system relies on manual methods such as using Microsoft Excel and a project website, which often leads to inefficiencies and human errors. Through the research, the author aims to develop a system that helps streamline project management processes by improving data management, communication, and efficiency. The design utilizes a Domain-Driven Design (DDD) approach with microservices architecture to ensure scalability, modularity, and effective management of multiple research projects. The system also integrates the 10 Knowledge Areas of PMBOK to ensure that the needs of the Research Department are met. The findings highlight that the proposed system could enhance project monitoring, reduce errors, and allow for a more effective project management workflow. This design proposes a microservices-based architecture that enables independent services for better system flexibility and scalability. The implementation of this system is expected to improve project performance and meet the operational needs of the XYZ Institute’s Research Department.